A first‐prototype multi‐determinant X‐ray constrained wavefunction approach: the X‐ray constrained extremely localized molecular orbital–valence bond method. Issue 4 (9th May 2017) - Genoni, Alessandro
Abstract : In this study, a first‐prototype multi‐determinant X‐ray constrained wavefunction approach is proposed. The new X‐ray constrained wavefunction is written as a linear combination of pre‐determined single Slater determinants constructed with extremely localized molecular orbitals. By exploiting experimental structure factors, the novel method enables one to extract resonance structure weights for molecules having a multi‐reference character. Abstract : All the current variants of Jayatilaka's X‐ray constrained wavefunction (XCW) approach work within the framework of the single‐determinant wavefunction ansatz . In this paper, a first‐prototype multi‐determinant XCW technique is proposed. The strategy assumes that the desired XCW is written as a valence‐bond‐like expansion in terms of pre‐determined single Slater determinants constructed with extremely localized molecular orbitals. The method, which can be particularly suitable to investigate systems with a multi‐reference character, has been applied to determine the weights of the resonance structures of naphthalene at different temperatures by exploiting experimental high‐resolution X‐ray diffraction data. The results obtained have shown that the explicit consideration of experimental structure factors in the determination of the resonance structure weights may lead to results significantly different compared with those resulting only from the simple energy minimization.